Implementation of PP NOMOR 23 TAHUN 2018 on the Tax Cmplianc of Micro, Small and Medium Enterprises (UMKM) in Semarang City - Putra Harjanto, Atta; ., Subowo; ., Kiswanto; Widodo, Hayat; Fitriani, Nani (KnE Social Sciences, 2020)
This research aims to examine the influence of the application of government regulation (PP) number23 of 2018 on tax compliance for Micro, Small and Medium Enterprises (UMKM) in Semarang city. Implementation of PP No.23 of 2018 is proxied by the variables of taxation knowledge and taxation sanctions. This is a quantitative research using primary data. The data are collected using questionnaire and analyzed using multiple regression. The data are processed using SPSS to analyze the data, and the research samples are selected using the questionnaire. The population of this research is the Micro, Small, and Medium Enterprises in Semarang, especially the Courses and Training institutions. There are 208 valid and reliable samples for further analysis. The results show that the application of PP No.23 of 2018 in Semarang affects the tax compliance of UMKM. This shows that the understanding of new regulations and sanctions positively influences the tax compliance among the UMKM. Due to the chosen research approach, the results are specific and may be less generalizable. Therefore, further researchers are encouraged to test the hypotheses submitted to other objects. This research includes implications for the tax regulators in implementing new regulations that are able to significantly influence the UMKM in the future. Keywords: Tax Knowledge, Tax Sanctions, Tax Compliance, PP Nomor 23/2018, UMKM